Cultural way of creating dances to promote the local values of the community - Rittibul, Pravit; Boontonglek, Manoch; Ngerndang, Artitaya; Nasom, Chananchida (International Journal of Innovative Research and Scientific Studies, 2025)
The research on the Cultural Way of Creating Dances to Promote the Local Values of the Community aims to examine the cultural capital related to city pillars to find formats and elements for presenting creative performances to promote communities’ values and local identity in a participatory manner in Pathum Thani Province through performing art and searching for ideas obtained after creating performance works. This study applied qualitative research methods, research processes and tools, study and survey data from academic documents, information media, field study and survey, interviews, and experiences of researchers and community leaders. The data obtained is analyzed and presented as academic biography and performance. The research found that The City Pillar Shrine was created by gathering those who had the strength and faith of the people to build the City Pillar Shrine in the style of the Fine Arts Department to serve as a stable place of worship and unity. This can be classified according to the elements of dance into 8 elements: 1) performance design into 3 periods, period 1 “History”, period 2 “Faith” and period 3 “Nong Suea people” 2) Selection of performers 3) Design of dance moves 4) Design of performance equipment 5) Performance Sound and music design, 6) costume design, 7) lighting design, and 8) performance space design. In addition, the researcher considered three ideas obtained after creating dance: 1) considering creativity in dance, 2) considering the use of symbols in creating dance, and 3) considering dance theory, music, and visual arts.